Antimicrobial use and multidrug-resistant Salmonella spp., Escherichia coli, and Enterococcus faecalis in swine from Northern Thailand - David C. Love (2018)
The aim of this study was to isolate antimicrobial-resistant bacteria from intensive commercial and backyard swine operations (farms) in Northern Thailand and to characterize antimicrobial usage among swine farmers. A total of 51 swine farms in Chiang Mai, Lampoon, and Nan provinces were visited from February to October 2011 to collect swine fecal samples for bacterial isolation (Salmonella spp., Escherichia coli, Enterococcus faecalis) and antimicrobial resistance testing. A survey about production intensity, management practices, animal health, and antimicrobial usage was conducted with a sub-set of farms (n = 20) located in Nan province. The farm-level prevalence of drug-resistant E. coli, E. faecalis, and Salmonella spp. was 96, 35, and 18%, respectively. Of the four surveyed commercial operations (median = 58 pigs/farm), 75% routinely administered antimicrobials to pigs ( > 50% of animal life). In the 16 backyard farms surveyed (median = 6 pigs/farm), 89% used antimicrobials intermittently (10-50% of animal life) or episodically ( < 10% of animal life) and one farm routinely administered antimicrobials to pigs. Herd size was moderately positively correlated (R2 = 0.44) to the number of resistance traits identified on a farm. These data indicate that reservoirs of multidrug resistance are widely present in swine farms of all sizes in Northern Thailand and may be affected by farm size and antimicrobial usage practices on the farm.